Evaluation of Internet-Based Interventions on Waist Circumference Reduction: A Meta-Analysis - Seo, Dong-Chul; Niu, Jingjing (JMIR Publications, 2015)
BackgroundInternet-based interventions are more cost-effective than conventional interventions and can provide immediate, easy-to-access, and individually tailored support for behavior change. Waist circumference is a strong predictor of an increased risk for a host of diseases, such as hypertension, diabetes, and dyslipidemia, independent of body mass index. To date, no study has examined the effect of Internet-based lifestyle interventions on waist circumference change. ObjectiveThis study aimed to systematically review the effect of Internet-based interventions on waist circumference change among adults. MethodsThis meta-analysis reviewed randomized controlled trials (N=31 trials and 8442 participants) that used the Internet as a main intervention approach and reported changes in waist circumference. ResultsInternet-based interventions showed a significant reduction in waist circumference (mean change -2.99 cm, 95% CI −3.68 to −2.30, I2=93.3%) and significantly better effects on waist circumference loss (mean loss 2.38 cm, 95% CI 1.61-3.25, I2=97.2%) than minimal interventions such as information-only groups. Meta-regression results showed that baseline waist circumference, gender, and the presence of social support in the intervention were significantly associated with waist circumference reduction. ConclusionsInternet-based interventions have a significant and promising effect on waist circumference change. Incorporating social support into an Internet-based intervention appears to be useful in reducing waist circumference. Considerable heterogeneity exists among the effects of Internet-based interventions. The design of an intervention may have a significant impact on the effectiveness of the intervention.